Screening, molecular identification, and evaluation the effects of indigenous Plant Growth-Promoting Rhizobacteria on growth indices and nutrient uptake of chamomile (Matricaria chamomilla) under saline conditions - Tafaroji, Seyed Hassan; Abtahi, Seyed Ali; Jafarinia, Mojtaba; Ebadi, Mehdi (Frontiers in Microbiology, 2025)
IntroductionSalinity is a major issue affecting agricultural lands, leading to reduced crop productivity and soil degradation. One approach to mitigate the effects of salinity is utilizing PGPR. This study aimed to isolate and identify indigenous PGPR from rhizosphere soil and evaluate their effects on the growth indices of chamomile under saline conditions.MethodsForty-five rhizosphere soil samples were collected from agricultural fields in Beyram, Iran. The PGPR were isolated and identified using standard phenotypic, biochemical, and molecular assays. Plant growth-promoting traits were applied for PGPR strain screening. The effects of selected PGPR strains on the growth indices and nutrient uptake of chamomile under saline conditions were evaluated in a greenhouse experiment.Results and discussionA total of 181 bacterial isolates were identified from the 45 soil samples, belonging to eight genera and 13 species. Seven species, including B. cereus, P. fluorescens, P. syringae, A. radiotolerans, P. phenanthrenivorans, P. alcaliphila, and L. macroides, possessing all five growth-promoting characteristics, were selected for further experiments. PGPR treatments significantly improved chamomile's growth, biochemical parameters, and nutrient uptake under different salinity levels. The P1 treatment at 2 dS.m−1 salinity had the highest root (16.75 cm) and shoot length (32.91 cm), along with dry root (0.089 g) and shoot weight (1.67 g). Biochemical improvements included higher chlorophyll and essential oil content with P2 at 2 dS.m−1. Increased salinity decreased overall plant growth and nutrient uptake. The indigenous PGPR strains showed promising potential to enhance chamomile growth and nutrient status under salt stress, offering a sustainable strategy for improving crop productivity in saline-affected regions.